PEDAGOGICAL COMPETENCES IN EDUCATION - HANZALOVA, Jana (Trends in education, 2008)
The report deals with analyses of pedagogical competences in project conception of common school and studies OECD. This report also involves the conception of pedagogical competences according to authors as Svec, V., Korthagen, F., Koetsier, Wubbels.
Keywords: education; pedagogical competences; pedagogue (educator)